2004
DOI: 10.1002/j.2334-5837.2004.tb00513.x
|View full text |Cite
|
Sign up to set email alerts
|

3.2.3 An Approach to Design for Safety in Complex Systems

Abstract: Most traditional hazard analysis techniques rely on discrete failure events that do not adequately handle software intensive systems or system accidents resulting from dysfunctional interactions between system components. This paper demonstrates a methodology where a hazard analysis based on the STAMP accident model is performed together with the system development process to design for safety in a complex system. Unlike traditional hazard analyses, this approach considers system accidents, organizational fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 4 publications
0
19
0
Order By: Relevance
“…Effective leaders make efforts to organize activities in such a way that they make better use of resources, information, and equipment; they plan activities, assign tasks, determine resource requirements, and coordinate interrelated activities (Dulac and Leveson, 2004). To achieve these goals, effective leaders need to apply a variety of different relation-oriented behaviors.…”
Section: Reference Frame Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Effective leaders make efforts to organize activities in such a way that they make better use of resources, information, and equipment; they plan activities, assign tasks, determine resource requirements, and coordinate interrelated activities (Dulac and Leveson, 2004). To achieve these goals, effective leaders need to apply a variety of different relation-oriented behaviors.…”
Section: Reference Frame Of the Studymentioning
confidence: 99%
“…emergent behavior (Leveson, 2002). The control processes that enforce these constraints must limit system behavior to the safe changes and adaptations implied by the constraints (Dulac and Leveson, 2004). Dulac and Leveson (2004) showed that as the complexity of engineered systems increases, hazard analysis techniques have continued to lag behind the state-of-the-art engineering practice.…”
Section: Reference Frame Of the Studymentioning
confidence: 99%
“…Hazard analysis is essentially the investigation of an accident before it occurs. A proactive accident investigation, i.e., hazard analysis, using STAMP rather than the traditional analysis techniques based on event-chain models (e.g., fault tree analysis, event tree analysis, and failure modes and effects criticality analysis) can provide the information necessary to design an integrated socio-technical system, including development and operations, to prevent accidents in software-intensive systems [6].…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 shows a categorization of control flaws that can lead to the violation of the four conditions above. This categorization can be used in the creation of new hazard and accident analysis techniques (see, for example, [14,6]). …”
Section: Control Flaws Leading To Hazardsmentioning
confidence: 99%
See 1 more Smart Citation